Intramyocardial block in patients with atrioventricular block. (7th March 2018) - Li, Guoliang; Saguner, Ardan M; Akdis, Deniz; Fontaine, Guy H
Abstract : Atrioventricular (AV) block has been extensively studied. However, conduction inside the myocardium in patients with AV block has not been reported. In this study, we aimed to demonstrate the presence of intramyocardial block in patients with AV block. Five consecutive patients with spontaneous high-grade AV block and Torsades de pointes (TdP) were prospectively studied with standard United States Catheter Instruments (USCI) endocardial temporary catheter located at the right ventricle (RV) apex. The morphology of endocardial potentials observed in the basic QRS complexes as well as during episodes of TdP was studied. The electrogram (EGM) of the basic rhythm showed a sharp deflection of high amplitude preceded and/or followed by a smooth potential of low amplitude interpreted as far-field potentials in all patients. The sharp potential can be observed at the beginning, in the middle or at the end of the smooth potential. All these potentials were reproduced from beat to beat and were falling inside the QRS complex of the surface ECG. Therefore, these aspects are zones of electrically depressed or silent myocardium larger than the interelectrode distance of 12 mm. This situation is in agreement with recent genetic factors. In this study, we demonstrated for the first time that patients with spontaneous AV block also have trouble in ventricular activation located on the AV conduction system and inside the myocardium. It is then possible to speculate that the presence of diffuse non-conducting myocardium explains why most TdPs do not degenerate into ventricular fibrillation (VF) and generally stop spontaneously.